Pengaruh asimetri informasi dan ukuran perusahaan terhadap manajemen laba pada perusahaan pertambangan yang terdapat di bursa efek indonesia - Anastasia Wenny Manggau (Faculty of Economics and Business Mulawarman University, 2016)
The research aims to investigate about asymmetric information and size of company toward earning management on mining companies which listed by Indonesia Stock Exchange for the period 2011-2013. The type of data used in this research is a secondary data that sourced by official website of Indonesia Stock Exchange. The analyisis Method used in this research is multiple linear regression analysis and helped by 21 version. The result of research partially shown that the variable of asymmetric information have a significant effect on earning management by result of the of 3,532 with significance level of 0,001. The reacerch result is supported by the research of Muliati (2011) which stated the asymmetric information has a positive significant effect on earnings management, while the size of company has no significant effect on earnings management with the -0,863 with a significance level of 0, 392 which the results of this research are also supported by previous study conducted by Limantara (2009) which states that the result of size of company is negatively affectively affect toward earning management. This research suggested the company to more effectively provide the financial reports and use many factors that effected to earning management beside total asset to measure the size of company.Keyword: Earning management, asymmetric information and size company